Pengembangan Permainan Edukasi Berbasis Kinect bagi Penderita Asperger Syndrome untuk Menangani Empathy Disorder - Dessy Amri Raykhamna; Tri Afirianto; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In Indonesia, the handling of empathy disorder in asperger syndrome sufferers was not welcomed by parents due to cost and transportation factors. In addition, treatment of empathy disorder in asperger syndrome sufferers is given the same treatment with other Autism Spectrum Disorder (ASD) classification. This research aims to develop Kinect-based educational game that can help a person with asperger syndrome in understanding feelings of the others, so that empathy toward each other can grow. At the end of 2013 until 2014, Kinect considered feasible for dealing with therapy and rehabilitation in people with neurological disease and Traumatic Brain Injury (TBI). In this research, Kinect applied in educational game that relies on the movement of the right hand. This research was tested on 5 asperger syndrome sufferers with empathy disorder. The results of this research achieved after asperger syndrome sufferers using Kinect-based educational game, that resulted increased score on each level and emotion, as well as descreased total Toronto Empathy Questionnaire (TEQ) of 12.8% from average of total TEQ before asperger syndrome sufferers using Kinect-based educational game.